International Transmission of Bank and Corporate Distress - N'Diaye, Papa.; Gray, Dale.; Oura, Hiroko; Tamirisa, Natalia (Washington, D.C. : International Monetary Fund, 2010)
The paper evaluates how increases in banks' and nonfinancial corporates' default risk are transmitted in the global economy, using in a vector autoregression model for 30 advanced and emerging economies for the period from January 1996 to December 2008. The results point to two-way causality between bank and corporate distress and to significant global macroeconomic and financial spillovers from either type of distress when it originates in a systemic economy. Corporate distress in advanced economies has a larger impact on economic growth in emerging economies than bank distress in advanced economies has. In contrast, activity in advanced economies is more vulnerable to bank distress than to corporate distress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet